Rehydration after exercise with fresh young coconut water, carbohydrate-electrolyte beverage and water - Ismail, Mohamed Saat (2001)
This is cross-over randomized study that assessed the effectiveness of fresh young coconut water (CW), carbohydrate-electrolyte beverage (CEB) and plain water (PW) for whole body rehydration and blood volume (BV) restoration during a 2 h rehydration period following exercise-induced dehydration. Eight healthy male volunteers between the ages of 20 to 30 years (22.4±3 years), with an average V02max of 45.79±1.52 mL. kg.-1.min:1 exercised at 60°10 of V02max at an environmental temperature of 31.1±0.03°C and relative humidity (rh) of 51.4±0.1 % for 90 minutes until 2.78±0.06°10 (1.56±0.05 kg) of their body weight (BW) was lost. After exercise, the subjects sat for 2 h in a thermoneutral environment (22.5±0.1°C; 67.0±1.0010 rh) and drank a volume of either CW, CEB or PW representing 120°/0 of the fluid lost. Fluids were consumed in three boluses, representing 50°10 (781±47 mL), 40°10 (625±33 mL) and 30% (469±28 mL) of the fluid lost, at 0, 30 and 60 min respectively of the 2 h rehydration period. Subjects remained fasted throughout the rehydration period. The drinks given were randomized and the exercise-induced dehydration were done at one-week intervals. The percent of body weight loss that was regained (used as index of percent rehydration) during CW, PW, and CEB trials was 75±5°10, 73±5°10, and 80±4 % respectively, but was not statistically different between trials. At the end of all the trials the subjects were somewhat hypohydrated (range 0.08-0.20 kg BW below euhydrated BW; p> 0.05) after the 2 h rehydration period since additional water and BW were lost as a result of urine formation, respiration, sweat and metabolism. The rehydration index, which provided an indication of how much of what was ingested actually was used for body weight restoration, was again not different statistically x between trials (1.56±O.14, 1.36±O.13 and 1.71±O.21 for CW, CEB and PW respectively). Although BV restoration was better with CW, it was not statistically different from CEB and PW. Cumulative urine output was similar in all trials: CW (394±75 mL), PW (351±47 mL) and CEB (325±69 mL). There were no differences at any time between the three trials in hemoglobin concentration, serum Na+ and cr, serum osmolality, urine output and net fluid balance. Urine osmolality decreased after 1 h during the rehydration period and it was lowest in PW trial. Plasma glucose concentrations were significantly higher when CW and CEB were ingested when compared with PW ingestion during the rehydration period. In conclusion, ingestion of fresh young coconut water, a natural refreshing beverage, could be used for whole body rehydration after exercise.